Bifidobacterium animalis subsp. lactis BB-12 Has Effect Against Obesity by Regulating Gut Microbiota in Two Phases in Human Microbiota-Associated Rats - Mao, Kemin; Gao, Jie; Wang, Xianghong; Li, Xiyu; Geng, Shuo; Zhang, Tuo; Sadiq, Faizan Ahmed; Sang, Yaxin (Frontiers in Nutrition, 2022)
Bifidobacterium animalis subsp. lactis BB-12 (BB-12) is an extensively studied probiotics species, which has been reported to improve the human gut microbiota. This study aimed to confirm the effects of BB-12 on high-fat diet (HFD)-induced gut microbiota disorders. The probiotic BB-12 was consumed by human microbiota-associated rats and changes in gut microbiota were compared using next generation sequencing of the fecal samples collected from the normal chow group, the HFD group, and the BB-12-supplemented group. The enterotypes switched from Prevotella dominant to Akkermansia dominant as a result of switching diet from normal chow to HFD. BB-12 conferred protection on the gut microbiota composition of the rats by increasing the abundance of Prevotella and decreasing the abundance of Clostridium, Blautia, and Bacteroides in 0–3 weeks. In addition, Prevotella-dominant enterotype was maintained, which provides improve obesity effects. A decrease in body weight and the Firmicutes/Bacteroidetes ratio were also observed at week 3. While in 4–8 weeks, the enrichment of short-chain fatty acids-producing bacteria such as Eubacterium and Parabacteroides and probiotics such as Bifidobacterium was observed. The results revealed that BB-12 against obesity by regulating gut microbiota in two phases. After a short-term intervention, BB-12 supplementation suppressed the transition from the healthy to obesity state by protecting Prevotella-dominant enterotype, whereas after a long-term intervention, BB-12 ameliorates obesity by enriching beneficial bacteria in the gut.